A 3.45 Gigabits/s SiPM-based OOK VLC receiver - Matthews, W; Ahmed, Z; Ali, W; Collins, S (Institute of Electrical and Electronics Engineers, 2021)
A relationship between irradiance and the current needed to maintain the bias voltage applied to a silicon photomultiplier (SiPM) is shown to agree with experimental data. In addition to showing the saturation of the SiPMs response this relationship can be used to determine the power consumed by an SiPM. In addition, results are presented which show that, because of its higher maximum photon count rate, a 30020 SiPM can achieve a bit error rate (BER) of 10 −3 at a data rate of 3.45 Gbits/s.